Optimasi Sintesis Asam 3-benzamido-4-metil benzoat (Optimization Synthesis 3-benzamido-4-Methyl Benzoic Acid) - Muh Agus Mauluddin; Dian Agung Pangaribowo; Indah Purnama Sa\ (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Benzoic acid derivative has been developed as new drugs that have antioxidant, antifungal, analgesic, anti-cancer, anti-inflammatory, and anti-herpes simplex virus activity. In this study, a new compound of benzoic acid derivative, 3-benzamido-4-methyl benzoic acid (3-BM) was synthesized by reacting 3-amino-4-methyl benzoic acid with benzoyl chloride. This study used benzoylation reaction with Schotten-Baumann method. Temperature, time, and TLC mobile phase were needed to be optimized to make optimum condition, so the synthetis reaction can be done. The reaction time was 24 hours, the samples were taken at 1,2,3,4,5,6,12,24 hours then spotted on TLC plates and eluated with optimum eluent chloroform: ethyl acetate: acetic acid (100:5:1). 3-BM compound can be synthesized by benzoylation reaction with optimum synthesis condition at room temperature 25-27 °C and 2 hours reaction time. Keywords: synthesis, benzoic acid derivative, 3-benzamido-4-methyl benzoic acid, benzoyl chloride